Aspergillus Proteolitik Indigenous dari Koji dan Kemampuannya Mendegradasi Aflatoksin B1 - Sardjono Sardjono; Endang Sri Rahayu; Sri Raharjo; Kapti Rahayu Kuswanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Legume and cereals are always exposed to the danger of fungal contamination. Among such fungi, some species of the genus Aspergillus are potential of aflatoxins producer. Aflatoxin BI (AFB1) which is the most carcinogenic mycotoxins , known very stable under cooking condition and other processing factors. The removal of AFB1 by degradation or detoxification is critical to reduce risk to human health. Microbiological degradation is a promising method for AFB1 degradation compared to others. The aim of this research was to isolate the proteolytic Aspergillus strain from